National lifestyle: Essence and content - Shokirovich, Boymurodov Zohid (Goodwood Publishing, 2025)
Purpose: This study aims to examine the transformation of lifestyles within the framework of socio-historical development, focusing on how ecological, economic, and cultural factors influence the evolution of human living patterns. The research seeks to identify the underlying causes of lifestyle diversity within the same historical period and to analyze its social and moral implications. Research Methodology: The study employs a historical-sociological approach combined with comparative and analytical methods. Data were gathered from archival sources, policy documents, and previous sociological studies that address social stratification, economic change, and cultural adaptation. By comparing different socio-economic groups and historical stages, the research explores how shifts in environmental conditions and economic systems reshape everyday life. Results: Findings reveal that variations in lifestyle are closely linked to the interaction between economic progress, environmental conditions, and cultural continuity. Rapid modernization and urbanization have altered traditional social values, creating disparities in living standards and forms of social behavior. However, national traditions and collective ethics continue to function as stabilizing forces that preserve cultural identity. Conclusions: The coexistence of multiple lifestyles within the same period reflects the transitional nature of modern society, where traditional and modern values intersect. Sustainable development requires balancing economic growth with cultural preservation and environmental awareness. Limitations: The study is primarily descriptive and limited to qualitative data without extended longitudinal measurement. Contribution: This research provides an integrative perspective on how socio-historical dynamics shape lifestyle transformations and offers insights for policymakers in social and cultural development.